Five-Year Survival Among Stage IIIA Lung Cancer Patients Receiving Two Different Treatment Modalities - Bilfinger, Thomas (Med Sci Monit, 2016)
BACKGROUND: Five-year survival rates among stage IIIA lung cancer patients range between 2% and 15%, and there is currently no consensus regarding optimal treatment approaches for these patients. The current investigation evaluated survival outcomes among stage IIIA lung cancer patients receiving 2 different treatment modalities, neoadjuvant chemotherapy followed by resection versus chemoradiation alone. MATERIAL/METHODS: This retrospective study is based on 127 patients attending the Lung Cancer Evaluation Center at Stony Brook Cancer Center between 2002 and 2014. Patients were treated either with neoadjuvant chemotherapy followed by resection or a regimen of chemoradiation alone. Kaplan-Meier curves were used to compare survival outcomes between groups and Cox proportional hazard models were used to evaluate treatment effects on survival, while adjusting for possible confounders. RESULTS: Approximately one-fourth (n=33) of patients received neoadjuvant chemotherapy followed by surgery, whereas 94 patients received definitive chemoradiation. Patients in the surgical group were found to be significantly younger than those receiving chemoradiation alone (60.1 vs. 67.9 years, respectively; p=0.001). Five-year survival among patients receiving preoperative chemotherapy followed by resection was significantly higher than that among patients receiving chemoradiation alone (63% vs. 19%, respectively; p<0.001), whereas the hazard ratio (HR) was 3–4 times greater in the latter group (HR=3.77, 95% confidence interval=1.87, 7.61). CONCLUSIONS: Findings from this study indicate that preoperative chemotherapy followed by resection can improve survival outcomes for stage IIIA lung cancer patients compared with chemoradiation alone. The results reflect a select surgical group of patients; thus, the data highlight the need to develop new therapies that may result in more patients being viable surgical candidates.